Doing grammar - Morenberg, Max (Oxford University Press, 2002)
This practical and compact guide is invaluable for students in advanced grammar courses and essential for all readers seeking to discover how the English language works. The author employs insights from contemporary linguistic theories and builds them into a coherent system firmly rooted in traditional models. Focusing on the idea that students learn grammar by actually "doing grammar," he provides down-to-earth explanations about the composition of English sentences, illustrating them at every step with diagrams and other visual models